Pengaruh Financial Attitude, Financial Knowledge, dan Financial Well-Being terhadap Financial Management Behavior: Peran Mediasi Locus of Control - Annisa Safitri; Wirmie Eka Putra; Muhammad Ridwan (Yayasan Jompa Research and Development, 2026)
This study aims to analyze the influence of financial attitude, financial knowledge, and financial well-being on financial management behavior, with locus of control as an intervening variable, among undergraduate Accounting students at the Faculty of Economics and Business, Universitas Jambi. This study is motivated by inconsistent prior findings regarding the role of financial well-being and locus of control in shaping students' financial behavior, indicating a research gap that warrants further empirical examination. A quantitative approach was employed, with a population of 790 students and a sample of 132 respondents selected through purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with SmartPLS 4.0. The results show that financial attitude, financial knowledge, and financial well-being have a positive and significant effect on financial management behavior, both directly and indirectly through locus of control as an intervening variable. These findings contribute theoretically by reinforcing the relevance of the Theory of Planned Behavior in explaining students' financial behavior, and offer practical implications for students, educational institutions, and future researchers in designing financial education programs that strengthen not only financial knowledge but also students' internal locus of control.